Cassava: practices and technologies to improve food security in sub-Saharan Africa - Nyasha Sakadzo; Andrew Tapiwa Kugedera; Njodzi Ranganai; Letticia Kudzai Kokerai (Cogent Food & Agriculture)
Orphan crops are underutilised and under researched crops. In many developing countries, these crops are essential for food, nutrition security, climate compliant and income generation. However, minimal resources and research time have been significantly allocated as they are associated with poor developing countries. The objective of this mini review is to present or highlight the contribution of orphan crops to sustainable food production in Africa by presenting best management practices and technologies for the production of the crops. Additionally, technologies and best management practices for cassava cultivation are also covered. Cassava feed millions of people as it is adapted to the local environments in which it is grown. However, in Sub-Saharan Africa the application of modern breeding of these crops is only in its infancy. Cassava can be used for flour preparation which is used for bread making in developing countries. Management practices for sustainable cassava production include computational models, dynamic crop growth simulations, resistant varieties, golden-fleshed cassava, breeding for quality, mechanized planting and harvesting, effective weed management, and mobile processing units for value addition. There is a need for policy makers in sub-Saharan Africa to review their agricultural policy so as to encourage production of drought-tolerant cassava.